Study of variation in prices of oral antiplatelet drugs available in Indian market - Rashmi, Abhilasha; Nerlekar, Sharmada; Rajeev, Kumar (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Coronary artery disease is one of the most prevalent causes of death and disability in developed and developing countries. There is a wide variation in the prices of oral antiplatelet drugs marketed in India. Thus, a study was planned to find out the variation in cost in the oral antiplatelet drugs available in India either as a single drug or in combination and to evaluate the difference in cost of various brands of the same antiplatelet drug by calculating percentage variation in cost. Methods: Cost of oral antiplatelet drugs manufactured by different pharmaceutical companies, in the same strength and dosage forms was obtained from “current index of medical specialties” October 2015-January 2016. The difference in the maximum and minimum price of the same drug manufactured by different pharmaceutical companies and percentage variation in cost per 10 tablets was calculated. Results: Percentage variation in cost for oral antiplatelet drugs marketed in India was found to be-clopidogrel 75 mg (1067.3%), clopidogrel 150 mg tablet (148.7%), prasugrel 5 mg (94.4%), aspirin 150 mg (69.8%), prasugrel 10 mg (54.8%), aspirin 75 mg (51.5%), clopidogrel 300 mg tablet (42.9%) and ticlopidine 250 mg (32%). The lowest percent cost variation found is ticagrelor 90 mg (0%). In combination therapy the highest price variation (235.6%) was found for aspirin (75 mg)+clopidogrel (75 mg) followed by aspirin (150 mg)+clopidogrel (75 mg) (24.2%). Conclusions: There is a wide difference in the cost of different brands of oral antiplatelet drugs available in India. The clinicians prescribing these drugs should be aware of these variations in cost to reduce the cost of drug therapy.